Precarious professional work : entrepreneurialism, risk and economic compensation in the knowledge economy - Styhre, Alexander (Palgrave Macmillan, 2017)
This book examines the new conditions under which professional work, often referred to as "knowledge-intensive work," is organised and how professional groups who have traditionally been granted jurisdictional discretion now have their work routines renegotiated. In the new economic regime of what has been called "investor capitalism" and under the influence of shareholder primacy governance, professional work is put under pressure to change. The author explores issues of increased financial and economic volatility, the pressure to outsource and offshore professional work and the increased supply of competitors with tertiary education degrees in the labour market. Examining both macroeconomic conditions and policy that inform and shape the domain of professional work, the book emphasises how the nature of professional work has changed since the 1980s and 1990s and argues that it is no longer a "safe haven" for a favoured group of elite workers. Precarious Professional Work underlines how the study of professions must constantly accommodate new economic conditions and managerial practices to better understand how professional work is dependent on and entangled with external social, economic, and political conditions.
Keywords: Precarious employment.; Professional employees.; Knowledge economy.; Entrepreneurship.; Capitalism.; Personnel management.; elektronické knihy; electronic books